Therapeutic plasma exchange as part of multimodal treatment of acquired hemophilia in a patient with concurrent acute intracerebral bleed and pulmonary embolism. Issue 7 (24th April 2017) - Wool, Geoffrey D.; Chapel, David; Treml, Angela; Miller, Jonathan L.
Abstract : BACKGROUND: Autoantibodies against Factor VIII (FVIII) define the rare but life‐threatening bleeding disorder acquired hemophilia A (AHA). Correction of FVIII deficiency and eradication of the factor inhibitor are the ultimate therapeutic goals in this disorder. Bypassing agents such as recombinant factor VIIa (rFVIIa) or FVIII inhibitor bypassing agent are often used to control coagulopathy before the inhibitor is eradicated. Bypassing agents carry a risk of thrombosis, however. CASE REPORT: We report a patient with newly diagnosed AHA and thalamic bleed who additionally had active atrial fibrillation and developed a segmental pulmonary embolism, limiting tolerable rFVIIa dosage. This patient with very‐high‐risk brain bleed and concurrent thrombosis on bypass agent represented a significant management dilemma for which we successfully utilized therapeutic plasma exchange (TPE) to reduce the inhibitor titer. RESULTS: FVIII inhibitor was undetectable and FVIII level was above the lower limit of normal within 12.5 days from starting TPE. While the patient ultimately died 24 days from admission for reasons unrelated to bleeding, his intracerebral hemorrhage was unchanged in size and no other bleeding morbidity was observed. CONCLUSION: This patient achieved eradication of FVIII inhibitor and did not have bleed expansion while receiving multimodal therapy including corticosteroids, rituximab, and TPE. We discuss the periprocedural risks of TPE in an acquired hemophilia patient and our multiteam management of that risk.